A study of the Drakenstein Local Municipality's five main urban economic sectors with special reference to the municipality's strategic objectives - Slinger, Ronel H. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Public and Development Management)--University of Stellenbosch, 2007.